2020
DOI: 10.21037/apm-20-2096
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab in combination with anlotinib achieved remarkable efficacy in a patient with driver-negative lung squamous cell carcinoma and PS of 4

Abstract: Patients with driver-negative non-small cell lung cancer (NSCLC) and performance status (PS) of 3-4 do not tolerate chemotherapy well. There is currently no suitable treatment plan, and best supportive care is offered to patients with PS of 3 or greater. Some retrospective studies have shown the poor efficacy of immune checkpoint inhibitors (ICIs) for advanced NSCLC patients with PS ≥2 regardless of PD-L1 expression. However, some recent studies suggest that the anti-angiogenic drug has an immunomodulatory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Anlotinib increases infiltration of T cells, NK cells and APC cells, and the combination of anlotinib and immunotherapy has a synergistic effect. 30 , 31 In addition, anlotinib has been shown to have synergistic effects with chemotherapy and targeted therapies. 32 , 33 Adverse effects of anlotinib monotherapy have been shown to be manageable in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Anlotinib increases infiltration of T cells, NK cells and APC cells, and the combination of anlotinib and immunotherapy has a synergistic effect. 30 , 31 In addition, anlotinib has been shown to have synergistic effects with chemotherapy and targeted therapies. 32 , 33 Adverse effects of anlotinib monotherapy have been shown to be manageable in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The patient received combination therapy including endoscopic recanalization of central airway followed by immunotherapy, which reduced tumor lesions and improved the PS score (180). Case reports have shown that immunotherapy was also effective in patients with a PS of 4 (181,182). Nevertheless, the role of immunotherapy in patients with poor PS scores needs to be further investigated.…”
Section: Immunotherapy (Recommendation Category: B; Level Of Evidence: 1b)mentioning
confidence: 99%